(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the key issues of forming a common space for technological interaction and cooperation within the Eurasian Economic Union (EAEU), with a focus on the role of Kyrgyzstan. The article analyzes the differences in the level of technological development of the participating countries, the lack of coordination in the field of R & D, legal and infrastructural barriers. Measures are proposed to integrate scientific, educational and business structures, including the creation of digital platforms, the unification of legislation in the field of intellectual property and the development of innovation infrastructure. Particular attention is paid to the role of the Ministry of Economy of the Kyrgyz Republic in the implementation of reforms aimed at simplifying administrative procedures, attracting investment and digitalizing business processes. The results of the study demonstrate that the formation of a common technological space can accelerate innovative growth, increase the competitiveness of the EAEU countries and deepen their economic integration.